Teachers' beliefs about the teaching of physical education in Guayaquil - Kelly Deysi Hernández Mite; María Esther Prados Megías; Elva Katherine Aguilar Morocho (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.